Roles of Labor Movements and Paths to Varieties of Capitalism in South Korea and Taiwan - Ngamarunchot, Bank (Journal of Social Sciences Naresuan University, 2021)
This article aims to discuss “incremental changes” and “varieties” of economic institutions by examining the experiences of South Korea and Taiwan as case studies for theory building. Core arguments are here. First, contestations between labor, the state, and businesses trigger institutional evolvement. Second, degree of militancy which is chosen by labor movements determine trajectories of labor institutions and varieties of capitalism. If the degree is high and labor movements are contentious, the economy evolves toward Liberal Market Economy (LME). In contrast, if the degree is low and labor movements are compromised, the economy progresses to Networked Market Economy (NME). These findings lead us to further debates related to the theory of institutional changes, varieties of capitalism, and dialectical relations within capitalism.